The Health Literacy Among Turkish University Students - Solak, Müjgan (Health & Research Journal, 2024)
Background: Health literacy is a very important indicator in determining the health level of individuals and society. Materials and Method: This descriptive and cross-sectional study aimed to determine the health literacy level of the university students. A total of 1171 students, who agreed to participate in the study, were included in the sample of the study. Data were collected using the Personal Information Form and the Turkish Health Literacy Scale-32. Number, percentage, t-test, chi-square, one-way variance, and Post Hoc tests were used for the evaluation of the data. Results: It was found out that of the students, 8.7% of them had inadequate levels of health literacy, 33.8% had problematic, 37.2% had sufficient and 20.3% had excellent. Of the students participating in the study, 9.8% of the female students had inadequate levels of health literacy, while 36.4% had problematic levels of health literacy. Conclusion: It was found that university students do not have the expected level of health literacy. It may be recommended to increase the health literacy levels of university students through training.